Adaptive Topology Reconfiguration from an Actor Failure in Wireless Sensor-Actor Networks. (25th February 2015) - Zhang, Shengfeng; Wu, Xiaobei; Huang, Cheng
Wireless Sensor-Actor Network (WSAN) usually consists of numerous sensor nodes and fewer actors, and the connectivity of interactors is critical to the whole network. Due to the hash deployed environments and limited energy supply, actor nodes may fail and impact the performance of the whole network. Since the failure of a cut-vertex will disrupt connectivity and divide the topology into disjoint segments, most of the previous researches have already considered this scenario. However, the impact of an abruptly actor's failure to the network will be far more than that. This paper focuses on the problem of an actor's failure and gives a more comprehensive view of the faulty actor, that is, not only restricts to the cut-vertex. Length-Aware Topology Reconfiguration Algorithm (LTRA) is proposed on the basis of two vital definitions named as length impact index (LII) and vertex cut set (VCS). LTRA is a hybrid method which selects a best candidate for each actor (if it has) and then initiates in a distributed manner. Main idea of this approach is that candidate will move to replace the faulty one once the failure occurs. In addition, the candidate is selected from one-hop neighbors of each actor. Finally, performance of LTRA is validated by extensive simulation experiments.